Epidemic of multiple Treponema pallidum strains in men who have sex with men in Japan: efficient multi-locus sequence typing scheme and indicator biomarkers - Sato, Wakana; Sedohara, Ayako; Koga, Michiko; Nakagama, Yu; Yotsuyanagi, Hiroshi; Kido, Yasutoshi; Adachi, Eisuke (AIDS research and therapy, 2024)
The challenges in culturing Treponema pallidum have hindered molecular-biological analysis. This study aims to establish a molecular epidemiological analysis of syphilis among Japanese men who have sex with men (MSM) and to investigate the relationship between bacteremia and associated pathophysiology. We used whole blood specimens from syphilis-diagnosed individuals in Tokyo, collected between February 2019 and June 2022. All individuals were MSM, and most were people with HIV (97.2%). We used a multi-locus sequence typing (MLST) scheme for epidemiological analysis. Sequences for MLST (TP0136, TP0548, and TP0705) were obtained. Out of 71 whole blood samples, 26 samples (36.6%) were positive for TP0136, and we sequenced three loci for MLST in 22 samples (31.0%). The most frequently detected sequence type (ST) was ST3 (n = 9), followed by ST6 (n = 6). Phylogenetic analysis revealed that 12 samples belonged to the SS14-like group (60%), and 8 samples belonged to the Nichols-like group (40%). Treponema pallidum subsp. endemicum (TEN), the cause of bejel was detected in three samples (12%). There was a significant association between TP0136 detection rate and C- reactive protein (CRP) (77.0% at a cut-off:0.5 mg/dL). Both SS14-like and Nichols-like strains were circulating concurrently, and TEN could have been sexually transmitted among MSM with HIV. Elevated CRP may indicate the presence of the pathogen in the blood.